Tengku Hassanal appointed as royal patron of UMP Volunteers - Siti Nur Azwin, Zulkapri (Star Publications (Malaysia) Berhad, 2022)
PEKAN: The Regent of Pahang Tengku Hassanal Ibrahim Alam Shah Al-Sultan Abdullah Ri'ayatudin Al-Mustafa Billah Shah has been appointed as the royal patron for the Universiti Malaysia Pahang (UMP) Volunteers.